2019
DOI: 10.1515/reveh-2019-0048
|View full text |Cite
|
Sign up to set email alerts
|

The effect of occupational exposure to petrol on pulmonary function parameters: a review and meta-analysis

Abstract: Abstract Introduction Exposure to petrol and gasoline can have harmful effects on the lungs. This review aimed to summarize the reported effects of this exposure on pulmonary function parameters. Methods Relevant studies were identified by a comprehensive search in PubMed, Scopus, Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…Therefore, it can increase the prevalence of respiratory complications among gas station workers. Also, in a meta-analysis conducted in 2019, it was determined that occupational exposure to gasoline fumes is a risk factor for lung function and the prevalence of respiratory complications [33]. These results are consistent with our study.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, it can increase the prevalence of respiratory complications among gas station workers. Also, in a meta-analysis conducted in 2019, it was determined that occupational exposure to gasoline fumes is a risk factor for lung function and the prevalence of respiratory complications [33]. These results are consistent with our study.…”
Section: Resultssupporting
confidence: 92%
“…These findings are consistent with the study conducted in Nigeria in 2016 [14]. Body mass index (BMI) is one of the most important factors affecting pollutant absorption because lipophilic volatile pollutants produced in gas stations are absorbed proportionally to both adipose mass and BMI [15]. The mean BMI of the participants was in the range of 24.45 kg/m 2 , which was not consistent with the study conducted in Egypt in 2023 [16].…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Gasoline is the most consumed product of crude oil refining, which contains at least 150 hydrocarbons, including alkanes (60-70%), aromatics (25-30%) and alkenes (6-9%). Gasoline vapors (GV) have been linked to various pathologies, such as lung disorders, hematotoxicity, and encephalopathies [1][2][3][4]. The results of many studies have also shown that employees of gas stations and refineries who are chronically exposed to GV are at high risk of developing lung, kidney, and bladder cancers [5][6][7], as well as hematological malignancies [8].…”
Section: Introductionmentioning
confidence: 99%
“…Biological monitoring and risk assessment associated with exposure to chemical toxicants at the work place can be evaluated by measuring indices of organ and systemic functions in the exposed populations. An inverse relationship has been reported between lung function indices and duration of exposure to gasoline fumes in occupationally exposed individuals (Moghadam, et al, 2019). Higher levels of biomarker of oxidative DNA damage (8-OHdG) have been reported in gasoline station attendants compared to controls (Fenga, et al, 2017), while elevation of lipid peroxidation products and oxidative stress have been demonstrated in petroleum attendants (Leong,2021).…”
Section: Introductionmentioning
confidence: 99%